Two Essays on Regional Economic Integration in East Asia - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 2004)
Regional economic integration in East Asia has gained momentum in the aftermath of the 1997 financial crisis and the escalation of international terrorism. In the first essay, the integration process in Europe and East Asia is compared briefly. This is followed by a discussion on the expansion process by the European Union and how East Asia can learn from this. In particular, the concern is how to integrate the CMLV countries in a meaningful way. Proposals deal with the impact of freer movement of natural persons, the Japan-ASEAN comprehensive economic partnership agreements, and the viability of core labor standards. The second essay is more straightforward. Criteria for successful exchange rate coordination are specified and the paper determines whether the Philippines has satisfied the criteria. The conclusion is that while monetary policy has been fairly stable, the weak fiscal position will prevent the Philippines from participating in regional exchange rate coordination.
Keywords: 330; regional monetary cooperation; regional economic integration; accession countries; human development; fiscal bind; Wirtschaftsintegration; Ostasien